Euthanasia Dipandang Berdasarkan Perspektif Hukum Islam dan Kode Etik Kedokteran Indonesia (KODEKI) - Intana Aji Safrima; Asiya Chaniatuttazkiya; Sza Sza Al Zahwa Noor Sandaga (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2024)
Euthanasia, or "good death," is a controversial practice and has sparked debate in many parts of the world. In a medical context, euthanasia refers to the act of ending a person's life to reduce suffering due to terminal illness or incurable medical conditions. In Indonesia, where the majority of the population is Muslim, this issue has become very relevant to the view of Islamic law which emphasizes the importance of preserving life as a gift from Allah. According to this view, euthanasia is contrary to the basic principles of Islam that value life and affirm that only Allah has the right to determine a person's death. On the other hand, the medical code of ethics puts forward the principles of non-maleficence (no harm) and beneficence (doing good), but in terminal cases, this leads to ethical dilemmas in cases where ending the patient's life is considered a way to reduce suffering. The practice also presents challenges in terms of patient autonomy and the obligation of doctors to respect their decisions. In this context, this study aims to explore euthanasia from the perspective of Islamic law and medical ethics, as well as analyze the relationship between these two aspects in the context of Indonesian society and culture, as well as the practical challenges faced by doctors and patients in dealing with this issue.